Menopausal Acne – Challenges And Solutions - Khunger N; Mehrotra K (Dove Medical Press, 2019)
Niti Khunger, Krati Mehrotra Department of Dermatology and STD, Vardhman Mahavir Medical College, Safdarjang Hospital, New Delhi, IndiaCorrespondence: Niti KhungerDepartment of Dermatology and STD, Vardhman Mahavir Medical College, Safdarjang Hospital, Ring Road, New Delhi 110029, IndiaEmail drniti@rediffmail.comAbstract: Although acne is a disease predominant in adolescence, it is being increasingly observed in adult life, including the menopausal period. The etiology of menopausal acne is multifactorial, with hormonal imbalance being the major culprit. There is a relative increase of androgens in the menopausal female that leads to clinical hyperandrogenism manifesting as acne, hirsutism and androgenetic alopecia. Other endocrine disorders including thyroid abnormalities, hyperprolactinemia and insulin resistance also play a role. Genetics, stress, dietary changes, lack of sleep and exercise and other lifestyle changes are implicated as trigger factors. Most menopausal women with isolated few acne lesions have normoandrogenic serum levels and do not require extensive investigations. However, baseline investigations including total testosterone are useful. Patients must also be evaluated for associated comorbidities such as obesity, diabetes, hypertension and dyslipidemia. A detailed history can help to exclude polycystic ovarian syndrome, late-onset congenital adrenal hyperplasia or medications as a cause of acne. The evaluation of menopausal acne and the approach to treatment depend on the severity of acne and associated features. In patients with mild acne without virilization, prolonged topical therapy is the mainstay of treatment. Though combined oral contraceptives are effective, they are relatively contraindicated in the postmenopausal period. Spironolactone is the first choice of therapy in the subset of patients that require oral anti-androgen therapy. Procedural treatment can be useful as it can also help in the treatment of associated acne scars and concomitant skin aging. It is also important to focus on lifestyle changes such as reducing stress, controlling obesity, having a healthy diet, exercise and proper skin care routine to reduce acne. The focus of this article is on the clinical presentation and management challenges of menopausal acne, which represents a special subtype of acne.Keywords: acne, adult, menopause, hormonal, hyperandrogenism